Bettering the lives of patients with end-stage renal disease with HomeChoice Claria with Sharesource: an interview with Dr. Bruce Culleton. (September 2015) - Culleton, Bruce
<x xml:space="preserve">Abstract</x> Interview with Dr. Bruce Culleton, Vice President, renal therapeutic area lead at Baxter by Tasnim Zahri (Commissioning Editor) I was fortunate enough to meet Dr. Bruce Culleton, Vice President, renal therapeutic area lead at Baxter (Deerfield, IL, USA), during the European Renal Association – European Dialysis and Transplant Association conference in London to discuss Baxter's newest dialysis system; the HomeChoice Claria automated peritoneal dialysis system with the Sharesource web-based connectivity platform. Recently awarded a CE mark, HomeChoice Claria with Sharesource is hoped to better the lives of patients with end-stage renal disease, enable effective connectivity between patients and clinicians and pave the way toward improved individualized care.